Arabic historical dialectology: linguistic and sociolinguistic approaches - Holes, Clive (Oxford studies in diachronic and historical linguistics, 2018)
This title explores the history and evolution of Arabic as a spoken language, from the Arab Conquests of the seventh century up to the present day. Each chapter focuses on a specific region, a wider group of dialects, or a linguistic feature of particular historical interest